Composition of Tree-Vegetation in Community Forests of Uttaranchal Himalayas - Dwivedi, V.K.; Raizada, A.; Dass, A. (Indian Journal of Agroforestry, 2020)
Phyto-sociological investigation was carried out in a community-managed forest in a micro watershed located in the Western Himalayas during Oct-Nov. 2003 and Feb-March, 2004 to analyze the composition of trees on different topo sequences. Grewia optiva was found widely distributed and dominating at Hill top and Valley sites with IVI of 12 and 52.58, respectively whereas Bauhinia veriegata with IVI value of 13.47 in Hill slopes. The highest relative density values were also recorded by Grewia optiva on Hill top (18.58) and Valley sites (20.58) and Bauhinia variegata in Hill Slopes (15.79). On the whole species diversity was higher on slopes (2.98) as compared to valley (2.68) and hill top (2.62). The overall dominance of Grewia optiva and Bauhinia veriegata in community managed micro watershed in the region is because these trees are used for fodder and hence propagated and protected.